1984
DOI: 10.1103/physrevb.30.5861
|View full text |Cite
|
Sign up to set email alerts
|

Recombination ina-Si: H: Transitions through defect states

Abstract: To obtain detailed information about recombination processes near room temperature in a-Si:H we have measured the steady-state and transient response of luminescence, light-induced ESR, and photoconductivity in lightly doped and undoped samples. T¹ low-energy luminescence is at a different energy in nand p-type a-Si:H, and has an intensity-dependent decay. The results lead us to propose a new modelthat the radiative transition is the capture of a majority carrier into a neutral dangling bond, having a low radi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

1987
1987
2013
2013

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(28 citation statements)
references
References 27 publications
2
26
0
Order By: Relevance
“…4 I 11/2 luminescence are 1.35 and 1.12 eV, respectively. An electron capture by a D o state, however, is expected to release only about 1 eV, corresponding to half of the optical bandgap due to the mid-gap location of the D o states [24]. This is confirmed by the temperature dependence of the dark electrical conductivity, as is shown in Fig.…”
Section: Resultssupporting
confidence: 50%
See 1 more Smart Citation
“…4 I 11/2 luminescence are 1.35 and 1.12 eV, respectively. An electron capture by a D o state, however, is expected to release only about 1 eV, corresponding to half of the optical bandgap due to the mid-gap location of the D o states [24]. This is confirmed by the temperature dependence of the dark electrical conductivity, as is shown in Fig.…”
Section: Resultssupporting
confidence: 50%
“…Fig. 2 shows the PL spectra of instrinsic, Nd-doped, and Er-doped a-Si:H:C, taken at 20 K. We observe a strong, broad luminescence peak from the intrinsic a-Si:H:C film in the 0.6-1.1 lm range that is typical of bandtail to bandtail transitions in a-Si:H and related films [24]. The apparent peaks near $0.7 and $0.9 lm are optical artifacts due to multiple reflections.…”
Section: Experimental Conditionsmentioning
confidence: 92%
“…Hence the enhancement of PL properties was attributed to the alteration of the electronic structure by the incorporation of substitutional defect states and the donor activity of silicon. Earlier, Street et al [30] reported that PL of hydrogenated amorphous silicon near room temperature occurred by recombination of dangling bonds and also because dangling bonds acted as luminescence sites. It is to be noted that recombination process in a-C:H is believed to be similar to that of a-Si:H [24]; so based on the above discussions it can be inferred that, as due to doping, the percentage of sp 3 hybridized carbon increases in our case, the number of carbon dangling bonds also increases.…”
Section: Photoluminescence Studymentioning
confidence: 98%
“…In a structurally less perfect or doped films (higher dangling bond density), another broadband peak appears at lower energies around 0.9 eV [12]. The precise value depends on the type of the doping [13]. Here, the recombination path occurs from the band tail to the dangling bond level which is usually located near the middle of the gap.…”
Section: Introductionmentioning
confidence: 95%